El Direccionamiento de los Nombramientos al Cuerpo Diplomático Ecuatoriano afecta a los intereses del Estado - Bustamante Bermeo, María Belén (2020)
This research work includes the conceptual, doctrinal and legal study on the appointed appointment to the Ecuadorian diplomatic corps, affecting the interests of the State. It has constituted a legal problem, imposing an ideology or establishing relations of political patronage to manage public positions of Ambassador or Consul General in the different Republics, omitting that the Organic Law of the Foreign Service imposes requirements that at present have been eluded by the Executive , leaving aside the conception that the functions that Diplomats fulfill in foreign territory is essential for international relations in the economic, cultural, academic, social, environmental and security fields to be executed for the development of Ecuador, therefore its Professionalization and capacity must be oriented to the fulfillment of the attributions, avoid improvisation and inadequate management due to their low knowledge. The political poder has influenced to designate who belongs to the social circle, family of the Executive, by the exclusive attribution to execute these appointments, it is necessary to protect the interests of the State and avoid the violation of the meritocracy, to avoid omissions and influences it crystallizes the Reform to the Organic Law of the Foreign Service, in the pertinent part so that under an unrestricted control the designations are made and in the case of violating the norm, a sanction is carried out for non-compliance with the written norm.